From History to the Future: The Chinese Experience in Margaret Cezair-Thompson's The True History of Paradise - Peng, Xu (College literature, 2023)
This essay examines the Chinese experience represented in Margaret Cezair-Thompson's 1999 novel The True History of Paradise . By analyzing the author's characterization of the Chinese migrant Mr. Ho Sing and his Afro-Chinese Jamaican daughter Cherry Landing, this essay first elucidates Afro-Chinese intimacy in late nineteenth-century Jamaica and then investigates Jamaican Chineseness in the 1960s and 1970s. It underscores middle-class Jamaican Chinese's economic advantage in their proximity to Jamaica's Creole identity, and illuminates what appears to be the author's proposition of a reconsideration of creolization that, instead of presuming anti-Blackness or encouraging Black radicalism, negotiates the political and cultural dichotomy between Creole nationalists and the Afro-Jamaican majority. Drawing upon Cezair-Thompson's literary reworking of the Jamaican Chinese experience, I conclude that The True History of Paradise rehearses the possibilities to envision the future for the diasporic Chinese, the Jamaican nation, and Caribbean literature.